Transition to circular economy in Brazil: A look at the municipal solid waste management in the state of São Paulo - Paes, Michel Xocaira; de Medeiros, Gerson Araujo [UNESP]; Mancini, Sandro Donnini [UNESP]; Ribeiro, Flávio de Miranda; Puppim de Oliveira, Jose A. (Emerald, 2019)
Purpose: The purpose of this paper is to evaluate how improvements in municipal solid waste management systems (MSWMS) can contribute to a transition toward circular economy (CE) in urban areas, outlining actions and guidelines for public policies. Design/methodology/approach: The research was carried out in three municipalities located in the state of São Paulo in terms of: diagnosis; elaboration of more positive scenarios in terms of CE and scaling of economic and environmental benefits; and outline actions and guidelines for public policies of MSWMS. Findings: In developing countries like Brazil, MSWMS can contribute to a transition toward a CE through new public policies and management practices, or even through the improvement of those that already exist. Examples of this are the integration of the informal sector of the recycling chain and service sector related to repairs of clothing, shoes, furniture and electronics as well as composting at the food production site. This could be strengthened by legal and financial mechanisms, training and carbon credit projects. Moreover, there is a need for integration of public policies between different levels of governments and sectoral policies. Originality/value: This paper developed a methodology to examine the potential for a transition toward a CE through the MSWMS in different scenarios and cities. This methodology allows to advance the implementation of the concept of CE in urban areas of developing countries and generating co-benefits to the local economy and the global environment.
Keywords: Circular economy; Municipal solid waste; Public policies